Saying It's So : A Cultural History of the Black Sox Scandal - Nathan, Daniel A. (Book collections on Project MUSE., 2003)
Publisher's description: The story of "Shoeless" Joe Jackson and his teammates purportedly conspiring with gamblers to throw the World Series to the Cincinnati Reds has lingered in our collective consciousness for more than eighty years. With baseball so closely linked to American values and ideals, the Black Sox Scandal of 1919 disenchanted baseball fans, changed the way Americans felt about the national pastime, and fostered changes in the game. Daniel A. Nathan's wide-ranging, interdisciplinary cultural history is less concerned with the details of the scandal than with how it has been represented and remembered by journalists, historians, novelists, filmmakers, and baseball fans. Offering insights into what different cultural narratives reveal about their creators and the eras in which they were produced, Saying It's So is a complex study of cultural values, memory, and the ways people make meaning. Addressing the relationship between cultural narratives and social reality, Nathan considers the media's coverage of scandal--from front-page attention to scathing commentaries and cartoons--when the story broke in 1920 and in the following years. He also examines how oral tradition reiterated the scandal before new narratives began to appear at midcentury. In a series of astute reflections on Bernard Malamud's novel The Natural, Eliot Asinof's popular history Eight Men Out, and the work of the historians David Voigt and Harold Seymour, Nathan sheds light on the ways cultural and historical meaning is produced. Also considered are representations of the scandal in popular fiction and film during the Reagan era, the popular tourist destination and baseball field in Dyersville, Iowa, created for the film Field of Dreams, Ken Burns's television documentary Baseball, and the country's reactions to the 1994-95 Major League Baseball strike.